PENGARUH PENGGUNAAN KONSENTRASI AIR KELAPA MUDA PADA PENGENCER NACL FISIOLOGIS TERHADAP KUALITAS SPERMATOZOA IKAN TAWES ( Puntius javanicus) - Muhammad Rizal; Farah Diana; Dewi Mariani (JURNAL PERIKANAN TROPIS, 2015)
This study aims to knowing influence using cocentration of coconut water in physiology of NaCl dilution to spermatozoa quality ofPuntius javanicus. This research was counducted at Meunasah Krueng Village, Beutong Subdistrict, Nagan Raya District from 18th – 20th May 2015. This study was using completely randomized design with 5 treatmentand 3 replication. Sample was saved in refrigerator (3 days) with temperature 4oC and it is oberved sample quality and data was collected in daily. Result of the study show water coconut concentration (7%) giving result for best quality of spermatozoa, where mortality index average of spermatozoa is up to 80,55%, viability value of spermatozoa is up to 65,88% and spermatozoa mortality is up to 23,88%. In addtion, coconut water in in physiology of NaCl dilution have been affecting to spermatozoa quality of Puntius javanicus.